2013
DOI: 10.1111/ocr.12030
|View full text |Cite
|
Sign up to set email alerts
|

Enamel roughness and incidence of caries after interproximal enamel reduction: a systematic review

Abstract: The aim of this study was to investigate the effect of interproximal enamel reduction (IER) on tooth surfaces regarding the level of enamel roughness after applying different IER methods and the caries risk of treated teeth. Seven electronic databases were systematically searched. Two independent reviewers rated the articles at every step according to predetermined eligibility criteria. Data on enamel roughness were pooled if the same IER method was used and arithmetic values were available. Data on occurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 22 publications
0
29
0
1
Order By: Relevance
“…The stripped enamel surface was found more susceptible to demineralization and more sensitive to hot and cold temperatures than intact surfaces 11,13) . Other studies, however on the other hand, suggested that IPR did not lead to increased caries risk in anterior and posterior teeth 2,14,15) . Although whether IPR increases the susceptibility of the abraded enamel to demineralization is still a matter of debate, it should be kept in mind that a reduction of a tooth's enamel coating might lead to impaired resistibility to acid, erosion, and attrition 5,9) .…”
Section: Introductionmentioning
confidence: 94%
“…The stripped enamel surface was found more susceptible to demineralization and more sensitive to hot and cold temperatures than intact surfaces 11,13) . Other studies, however on the other hand, suggested that IPR did not lead to increased caries risk in anterior and posterior teeth 2,14,15) . Although whether IPR increases the susceptibility of the abraded enamel to demineralization is still a matter of debate, it should be kept in mind that a reduction of a tooth's enamel coating might lead to impaired resistibility to acid, erosion, and attrition 5,9) .…”
Section: Introductionmentioning
confidence: 94%
“…, ; Koretsi et al . ) and that it is possible to prevent mineral loss and promote remineralization (Alessandri Bonetti et al . , 2014; Uysal et al .…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative Scanning Electron Microscopy (SEM) evaluations showed that all the IER methods affect enamel morphology, leaving furrows and scratches and produce a significantly rougher surface compared to intact enamel (Zachrisson et al 2007(Zachrisson et al , 2011Koretsi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the technique used is perfectly safe. IPR has been shown to have no impact on the incidence of tooth decay or on distances between the roots of the teeth . Few patients complain of postoperative tenderness .…”
Section: Discussionmentioning
confidence: 99%
“…IPR has been shown to have no impact on the incidence of tooth decay or on distances between the roots of the teeth. 8,13 Few patients complain of postoperative tenderness. 14 Should they do so, they can be given fluoride treatment.…”
Section: Patient-driven Considerationsmentioning
confidence: 99%